2022
DOI: 10.3390/jcm11216515
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Cervical Lordosis Rehabilitation for Nerve Root Function and Pain in Cervical Spondylotic Radiculopathy: A Randomized Trial with 2-Year Follow-Up

Abstract: Sagittal cervical alignment is a clinically related feature in patients suffering from chronic cervical spondylotic radiculopathy (CSR). We designed this randomized trial to explore the effects of cervical lordosis (CL) correction in thirty chronic lower CSR patients with CL < 20°. Patients were assigned randomly into two equal groups, study (SG) and control (CG). Both groups received neck stretching and exercises and infrared radiation; additionally, the SG received cervical extension traction. Treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…The patient lies flat on their back (supine) on the ground with their legs extended and arms by their sides. The patient is encouraged to relax while lying on the Denneroll [ 15 , 16 ]. The denneroll was placed on the ground and positioned in the posterior aspect of the neck depending on the area to be addressed, as shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The patient lies flat on their back (supine) on the ground with their legs extended and arms by their sides. The patient is encouraged to relax while lying on the Denneroll [ 15 , 16 ]. The denneroll was placed on the ground and positioned in the posterior aspect of the neck depending on the area to be addressed, as shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The technique utilizes both mirror image ® adjusting/manipulation, exercises, and the unique extension traction procedures [ 11 , 12 , 13 ]. Meanwhile, the mirror image refers to the reversal of the spine and posture in the opposite direction of the present malalignment during the performance of rehabilitative procedures; the unique extension traction methods are for restoring normal lordosis and reducing forward head posture [ 11 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been numerous studies demonstrating the chronic effect of abnormalities of the cervical lordosis both in cervical spine trauma scenarios and degenerative spine disorders. The consequences for long-term increases in pain, loss of function, and increased risk for disability have been detailed in the surgical [50], MVC [18][19][20][21], and conservative care rehabilitation literature [51,52]. Further, studies have shown that both non-surgical and surgical improvement in cervical lordosis is a desirable clinical goal of care, with significant short-and long-term improved outcomes [50][51][52].…”
Section: Loss Of Lordosis In Mvc Populationsmentioning
confidence: 99%
“…If not adequately addressed, the pain and other symptoms of the cervical spine can progressively worsen, leading to a range of physical health issues such as spinal disc degeneration, musculoskeletal pain, and reversed cervical lordosis [ 2 ]. Cervical spine disorders include cervicogenic headaches [ 3 ], cervicogenic dizziness [ 2 ], cervicogenic angina and dyspnea [ 4 , 5 ], facial pain [ 6 ], fibromyalgia [ 7 ], visual disturbance [ 8 , 9 ], and cervical radiculopathy [ 10 , 11 ], which often present with a combination of painful symptoms and spinal dysfunction.…”
Section: Introductionmentioning
confidence: 99%